SKALA PENGUKURAN KUALITAS LAYANAN: SEBUAH KAJIAN LITERATUR - Dewa Nyoman Benni Kusyana; Komang Ary Pratiwi (Widya Manajemen, 2019)
Service quality measurement techniques along with dimensions of service quality have become a major issue in the marketing literature over the past few decades. The increasing importance of quality services, both practitioners and scholars began to focus on service delivery. Measurement of service quality is now seen as an important measurement tool for companies to understand the needs and desires of customers by analyzing customer satisfaction and experience with the services provided. Although until now there has been no agreement on a particular model that should be used to measure service quality, the fact is there are several effective models that can be used by both practitioners and scholars that have been produced by researchers. Until now, researchers believe and agree that service quality is multilevel or multidimensional. This study focuses on various types of service quality models that existed until year of 2000. The methodology used is conducting a review of service quality literature. The limitation of this literature review is that the existing service quality model was developed before 2000 because after 2000 the development of quality services was focused on the quality of electronic services.